THE MODEL OF LEARNING ANALOGY AND ITS EFFECT ON THE MASTERY OF THE CONCEPT IMMUNITY SYSTEM - Muh. Agung Givari; Suarga Suarga; Ahmad Ali (International Conference on Social and Islamic Studies, 2021)
This research means to determine the effect of the analogy learning model on the ability to mastery the biological concepts of class XI students at the Islamic Boarding School MA As'adiyah Dapoko Bantaeng. This research is the type of quasi-experimental (Quasi-Experimental Research) with a Non-Equivalent Control Group Design. The population in this study were all students of class XI. The sampling in this study used a purposive technique so that XI MIA 1 was selected as the control group and XI MIA 2 as the experimental group. Each class has 20 students. The instrument used to collect data research is a concept mastery test consisting of a pretest and postest, then the data is analyzed by descriptive and inferential through independent-sample t-test. The results show that the average posttest value of students in the experimental group was 67.30. In contrast, the control group was 54.20. then the sig. (2-Tailed) 0.000 <0.05 so that means there was an effect of the analogy learning model on the mastery of the concept immunity system of class XI students at the Pondok Pesantren MA As'adiyah Dapoko Bantaeng.